2005
DOI: 10.1038/sj.sc.3101888
|View full text |Cite
|
Sign up to set email alerts
|

Cervical angina: a seemingly still neglected symptom of cervical spine disorder?

Abstract: Design: A review of 10 surgical cases with symptoms of cervical angina. Objective: To stress the importance of symptoms of cervical angina in patients with cervical spine disorders. Setting: Fukui University Hospital, Japan. Results: A total of 10 patients complaining of symptoms of cervical angina were admitted with a tentative diagnosis of coronary artery disease. Pain relief was achieved by anterior surgical decompression in all patients. Conclusion: We stress that physicians should be aware of the symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(85 citation statements)
references
References 13 publications
(16 reference statements)
0
70
0
15
Order By: Relevance
“…The radiological criteria and definition, including segmental instability, have been described in more detail in our previous publications. 13,15 The type of spinal cord compression from a force acting from in front was classified on T2-weighted MR images and intraoperatively confirmed as a medial, paramedial, or foraminal lesion (Fig. 1).…”
Section: Radiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiological criteria and definition, including segmental instability, have been described in more detail in our previous publications. 13,15 The type of spinal cord compression from a force acting from in front was classified on T2-weighted MR images and intraoperatively confirmed as a medial, paramedial, or foraminal lesion (Fig. 1).…”
Section: Radiological Studiesmentioning
confidence: 99%
“…The cervical spine anterior decompression procedure has been described in detail in our previous reports. 2,13,15,18 Briefly, the affected discs were exposed using a left-sided anterolateral approach, and ~ 1.8-to 2.2-cm-wide vertebral resections were performed. Decompression was accomplished using a diamond bur (1-2 mm in diameter) to remove the posterior cortices of the vertebrae and endplates, herniated discs, and the deep and superficial layers of the posterior longitudinal ligament, which required a surgical microscope (OPM16CFC, Carl-Zeiss).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…They include rest, drugs, physiotherapy and exercise and manipulation 19 . Sometimes injecting medication (corticosteroids and a local anesthetic) into the joints of the spine may be needed 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of cervical angina can be explained by the fact that cervical neural roots from C4 to C8 contribute to the sensory and motor innervations associated with anterior chest pain, and patients with true cervical angina are more likely to have disease at the C6 and/or C7 level [2,4]. Some reports have indicated that anterior cervical surgery to correct nerve root or spinal cord compression can be a useful option for pain relief [1,3,5]. A few cases have been reported in which cervical angina was caused by spinal cord tumors such as ependymoma [6], atlantoaxial instability [7], or spinal cord infarction [8] without cervical spondylosis.…”
Section: Introductionmentioning
confidence: 99%